Biopreservative effect of the natural antimicrobial substance from Lactobacillus paracasei subsp. tolerans FX-6 on fresh pork during chilled storage. (October 2015) - Miao, Jianyin; Peng, Wendie; Liu, Guo; Chen, Yunjiao; Chen, Feilong; Cao, Yong
Abstract: The natural antimicrobial substance from Lactobacillus paracasei subsp. tolerans FX-6 was found containing novel bacteriocin with broad-spectrum antimicrobial activity to inhibit fungi and bacteria in our previous research. In present study, the biopreservative effect of the antimicrobial substance on quality and shelf life of fresh pork stored for 16 days at 4 °C were investigated based on the microbial (total viable counts), chemical (TVB-N, pH), and sensory evaluation. The five treatments evaluated included a control (sterile distilled water), 0.5% potassium sorbate solution and three levels of antimicrobial substance solution (0.15%, 0.6% and 1.2%). The antimicrobial substance could retain the good quality and extend the shelf life pork during storage and 1.2% antimicrobial substance could extend the shelf life to 12 days and the meat showed good characteristics. These results indicate that the antimicrobial substance has great potential as a natural biopreservative in chilled pork. Highlights: Natural antimicrobial substance from lactic acid bacteria was used to evaluated the biopreservative effect on fresh pork. Microbiological, chemical and sensory attributes were analyzed periodically at 4 °C for 16 days. 1.2% antimicrobial substance could extend the shelf life of fresh pork to 12 days.